2015
DOI: 10.1002/bdra.23435
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose maternal warfarin intake resulting in fetal warfarin syndrome: In search for a safe anticoagulant regimen during pregnancy

Abstract: We emphasize the need for optimizing the choice and dosage schedule of anticoagulants during pregnancy, least harmful for the mother and her developing fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 14 publications
0
17
0
5
Order By: Relevance
“…Recent prospective studies merely detected fetal malformation, and warfarin embryopathy was only observed in a twin among the cases included in our meta‐analysis, the risk of the teratogenic effect of warfarin might be overestimated. Nevertheless, Basu reported four cases of fetal warfarin syndrome born to mothers with rheumatic heart disease on warfarin prophylaxis during pregnancy at a dose <5 mg/d, the incidence of warfarin embryopathy differed perhaps because the diagnoses were based on autopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent prospective studies merely detected fetal malformation, and warfarin embryopathy was only observed in a twin among the cases included in our meta‐analysis, the risk of the teratogenic effect of warfarin might be overestimated. Nevertheless, Basu reported four cases of fetal warfarin syndrome born to mothers with rheumatic heart disease on warfarin prophylaxis during pregnancy at a dose <5 mg/d, the incidence of warfarin embryopathy differed perhaps because the diagnoses were based on autopsies.…”
Section: Discussionmentioning
confidence: 99%
“… Based on RCOG; Wallace and Swallow; Nelson‐Piercy; Meacham et al; Jeffery et al; RCOG; Basu et al; Esposito et al; Rosendahl et al …”
Section: Cancer and Pregnancymentioning
confidence: 99%
“…Antepartum and postpartum hemorrhages are more common in anticoagulated patients. Anesthetic and operative complications can occur and spinal or epidural anesthesia are often contraindicated 112,114 Recurrence or secondary malignancy in pregnancy Treatment in pregnancy Increased pregnancy loss if treated in embryonal stage 113 Ovarian tissue cryopreservation and transplant, and reintroduction of primary cancer risk Patients with ovarian tissue cryopreserved before treatment who then receive this tissue back to restore fertility are at risk of the reintroduction of their primary cancer from the transplanted tissue 115 Based on RCOG; 105 Wallace and Swallow; 108 Nelson-Piercy; 109 Meacham et al; 110 Jeffery et al; 111 RCOG; 112 Basu et al; 113 Esposito et al; 114 Rosendahl et al 115 be systemically healthy enough to cope successfully with the physiological changes of both the antenatal and postnatal periods. In both sexes, there are multiple potential sites for disruption and damage to occur in the process of reproduction and different treatments and modalities may impact fertility at different sites and in different ways.…”
Section: Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Teratogenic effect is dose-correlated and doses inferior to 5 mg/day seem to be safer, although teratogenic effect has been described also for these doses. [156][157][158] The greatest risk of teratogenic effects is present when warfarin is assumed between 6 th and 12 th week of gestation, 150 although toxicity is possible before or after this period. [159][160][161][162] Typical abnormalities caused by warfarin assumption are chondromalacia punctata, with stippled epiphyses and nasal and limb hypoplasia 150 and central nervous system abnormalities (e.g., optic atrophy, microcephaly, mental retardation, spasticity, and hypotonia).…”
Section: Warfarin and New Oral Anticoagulantsmentioning
confidence: 99%